Macrofauna community of the cold seep area at Site F, South China Sea - Wang, Haining; Wang, Xiaocheng; Cao, Lei; Zhong, Zhaoshan; Luan, Zhendong; Li, Chaolun (Frontiers in Marine Science, 2023)
A cold seep is one of the typical deep-sea chemical energy ecosystems and a hotspot for studying unique life processes and biogeochemical cycles in the deep sea. Macrofauna, which is one of the most important components of the cold seep ecosystem, has not been thoroughly studied. We examined the macrofauna community at Site F using images collected in 2016 by an imaging and laser profiling system and biological samples collected in 2020 and 2021 by TV grab and a remotely operated vehicle. In total, 41 species were found. The overall number of macrofauna identified at Site F (20,000 m2) reached 252,943 individuals, and the biomass reached 726.15 kg by dry weight. As the dominant species, Gigantidas platifrons and Shinkaia crosnieri reached their highest densities of 629 and 396 individuals/m2, respectively. The comparisons between different stations revealed that the diversity and density, even the biomass of dominant species, were much higher in the south than in the north at Site F in 2020. Correlation analysis showed that methane had a positive effect on macrofauna density. Compared with S. crosnieri, G. platifrons seems to be more adapted to the harsh cold seep environment. Methane consumption rates of the dominant species show that macrofauna are important in influencing seafloor methane fluxes. Our findings provide valuable insights into the ecology, community structure, and biota-environment interaction in the cold seep at Site F.